"Comprovisation": The Various Facets of Composed Improvisation within Interactive Performance Systems. - Dudas, Richard (Leonardo Music Journal, 2010)
This article discusses the balance between composition and improvisation with respect to interactive performance using electronic and computer-based music systems. The author uses his own experience in this domain in the roles of both collaborator and composer as a point of reference to look at general trends in "composed improvisation" within the electronic and computer music community. Specifically, the intention is to uncover the limits and limitations of improvisation and its relationship to both composition and "composed instruments" within the world of interactive electronic musical performance.